Positive Aspects of Digitalization of the Economy and its Networks - Kuldashev Farid G‘ulom o‘g‘li. (Zien Journals, 2023)
Nowadays, techniques and technologies are evolving. This article highlights the digitization of the economy and its sectors and the introduction of new techniques and technologies
Keywords: economics; digital economy; digitization; digital technologies